Sensory processing disorder in Saudi children with and without neuro developmental disorders - Dr. Ahmed Ali Alghamdi; Reham Abdullah Alhamyani; Sabah Hamad Al-jead; Dr. Rawan Abdullah Alhamyani; Reem Amer Alotaibi; Mansour Saad Althobaiti (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: Sensory processing disorder (SPD) is commonly associated with neurodevelopmental conditions such as attention-deficit/hyperactivity disorder (ADHD), autism spectrum disorder (ASD), and global developmental delay. This study aimed to evaluate the sensory profiles of Saudi children with and without neurodevelopmental disorders (NDDs) and to explore the influence of demographic factors such as age and gender on these profiles. Methods: This cross-sectional study was conducted at Center for Developmental and Behavior Disorders from 1/9/2024 to 1/11/2024. It included 83 Saudi children, comprising 49 children diagnosed with NDDs and 34 typically developing (TD) children. SPD was assessed in the participants using the Short Sensory Profile.Statistical analysis included gamma coefficients to compare sensory dimensions between the two groups, as well as to assess the strength and direction of associations between gender and the ordinal sensory dimensions. Additionally, ANOVA was employed to examine associations between age groups and sensory dimensions. Results: Among NDDs, ADHD was the most common diagnosis (25.3%), followed by autism (15.7%). Children with NDDs showed significantly higher rates of sensory processing challenges compared to TD children, with the strongest deficits observed in auditory filtering (gamma = -0.785, p = 0.0005) and under-responsiveness/seeks sensation (gamma = -0.764, p = 0.0005). Age had no significant effect on most sensory dimensions, except for under-responsiveness/seeks sensation in children with NDDs (p = 0.045). Gender was associated with movement sensitivity in TD children (p = 0.047) and taste/smell sensitivity in children with NDDs (p = 0.036). Conclusion: The findings highlight significant sensory processing challenges in children with NDDs, particularly in auditory filtering and sensory seeking behaviors. Age- and gender-specific variations emphasize the need for tailored, collaborative interventions among parents, teachers, and healthcare providers to enhance sensory processing and improve developmental outcomes and quality of life.